Anatomic Variation of the Optic Strut: Classification Schema, Radiologic Evaluation, and Surgical Relevance - Kerr, Robert G.; Tobler, William D.; Leach, James L.; Theodosopoulos, Philip V.; Kocaeli, Hasan; Zimmer, Lee A.; Keller, Jeffrey T. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective Anatomic variability of the optic strut in location, orientation, and dimensions is relevant in approaching ophthalmic artery aneurysms and tumors of the anterior cavernous sinus, medial sphenoid wing, and optic canal.Methods In 84 dry human skulls, imaging studies were performed (64-slice computed tomography [CT] scanner, axial view, aligned with the zygomatic arch). Optic strut location related to the prechiasmatic sulcus was classified as presulcal, sulcal, postsulcal, and asymmetric. Morphometric analysis was performed.Results The optic strut was presulcal in 11.9% specimens (posteromedial margin bilaterally anterior to limbus sphenoidale), sulcal in 44% (posteromedial part adjacent to the sulcus's anterior two thirds bilaterally), postsulcal in 29.8% (posteromedial margin posterior to the sulcus's anterior two thirds), and asymmetric (left/right) in 14.3%. Optic strut length, width, and thickness measured 6.54 ± 1.69 mm, 4.23 ± 0.69 mm, and 3.01 ± 0.79 mm, respectively. Optic canal diameter was 5.14 ± 0.47 mm anteriorly and 4.79 ± 0.64 mm posteriorly. Angulation was flat (>45 degrees) in 13% or acute (<45 degrees) in 87% specimens.Conclusions Anatomical variations in the optic strut are significant in planning for anterior clinoidectomy and optic-canal decompression. Our optic strut classification considers these variations relative to the prechiasmatic sulcus on preoperative imaging.
Keywords: optic strut; optic canal; anatomy; morphometric analysis; prechiasmatic sulcus